Efficacy and safety of sodium zirconium cyclosilicate for hyperkalaemia: the randomized, placebo‐controlled HARMONIZE‐Global study. (15th January 2020) - Zannad, Faiez; Hsu, Bang‐Gee; Maeda, Yoshitaka; Shin, Sug Kyun; Vishneva, Elena M.; Rensfeldt, Martin; Eklund, Stefan; Zhao, June
Abstract: Aims: Sodium zirconium cyclosilicate (SZC, formerly ZS‐9) is a selective K + binder to treat adults with hyperkalaemia. HARMONIZE‐Global examined the efficacy and safety of SZC among outpatients with hyperkalaemia from diverse geographic and ethnic origins. Methods and results: This phase 3, randomized, double‐blind, placebo‐controlled study recruited outpatients with serum K + ≥5.1 mmol/L (measured by point‐of‐care i‐STAT device) at 45 sites in Japan, Russia, South Korea, and Taiwan. Following open‐label treatment with thrice‐daily SZC 10 g during a 48 h correction phase (CP), patients achieving normokalaemia (K + 3.5–5.0 mmol/L) were randomized 2:2:1 to once‐daily SZC 5 g, SZC 10 g, or placebo during a 28 day maintenance phase (MP). The primary endpoint was mean central‐laboratory K + level during days 8–29 of the MP. Of 267 patients in the CP, 248 (92.9%) entered the MP. During the CP, mean central‐laboratory K + was reduced by 1.28 mmol/L at 48 h vs. baseline ( P < 0.001). During the MP (days 8–29), SZC 5 and 10 g once‐daily significantly lowered mean central‐laboratory K + by 9.6% and 17.7%, respectively, vs. placebo ( P < 0.001 for both). More patients had normokalaemia (central‐laboratory K + 3.5–5.0 mmol/L at day 29) with SZC 5 (58.6%) and 10 g (77.3%) vs. placebo (24.0%), with the greatest number of normokalaemic days in the 10‐g group. The most common adverse events with SZC were mild or moderate constipation and oedema. Conclusions: Normokalaemia achieved during the CP was maintained over 28 days with SZC treatment among outpatients with hyperkalaemia.